(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Seasonal variations in environmental factors have a significant impact on genotypic expressions in forms of the phenotypic outputs in silkworm crops, such as a cocoon’s weights, shell’s weights, & cocoon’s shells ratios. Necessity for the temperature & relatives humilities controls for sustainable cocoon formation is highlight by change in the environment variables from the day-to-day and the season to the season. Effect of the temperatures & humid on the silkworm’s growths & developments, as well as current findings on heat shock protein, is discussed in depth in this review study. The impact of air and light on silkworm growth is also discussed in the study. In addition, the effect of different environmental variables on the embryonic developments of the silkworm’s eggs, nutrition indices of the silkworm’s larvae, & the generative potentials of the silkworm moths is highlighted in this study. The researchers also discuss need for the cautions when the spinning silkworm & impacts of the temperatures & humidity on the silkworm post-cocoon the parameters. Future ideas for managing climatic conditions for a good cocoon crop were addressed in the study.